Electrical Properties of Rare Earth Chalcogenides Under the Effect of Pressure - Adhikari, D.R.; Adhikari, S.K.; Singh, V.K. (Kathmandu University Journal of Science, Engineering and Technology, 2007)
The numerical analysis of electrical properties involved in transport mechanism such as carrier concentration, carrier mobility, carrier effective mass, electrical resistivity and electrical conductivity for some rare earth chalcogenides is discussed. The formulae are derived and used to obtain numerical values of these electrical parameters, which are useful to describe the electrical behavior (insulating, semiconducting and metallic) of rare earth chalcogenides.